Job Mobility and Sorting: Theory and Evidence - Damir Stijepic (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
I derive a measure of job mobility that reflects individuals ability to sort into the preferred jobs. Relying on the Survey of Income and Program Participation, I find that educational attainment tends to have a strong positive effect on internal (i.e., within firms) and external (i.e., between firms) job mobility. General experience and occupation-specific human capital have only a limited effect on both internal and external mobility. The impact of being versatile on an individual s external job mobility is substantial and similar in magnitude as the effect of a college degree on a high school dropout s external mobility.
Keywords: J62; J24; I24; 330